PROBLEMATIKA PEMBELAJARAN JARAK JAUH DI MIN 3 TANGERANG - Hariyah Hariyah; Rini Anggraeni; Siti Khoeriyah (Jurnal Statement : Media Informasi Sosial dan Pendidikan, 2021)
Distance learning during the covid-19 pandemic was implemented by all schools so that several problems were found that were faced by teachers, students and parents. Distance learning, the role of parents is very necessary to support the smooth teaching and learning activities. A learning method in which the teaching process occurs separately from the learning process so that communication between teaching staff and students must be facilitated by printed materials, electronic media, and other media. During the COVID-19 pandemic, teachers are required to learn about information technology so that in providing learning it is not boring and creates enthusiasm for learning for students